Study of prevalence of work related stress and co-morbidities and its effect on work performance in KSRTC workers of Dakshina Kannada district, Karnataka, India - Prabhu, Sudhir; Shetty, Kiran; D’Cunha, Delma; Karkada, Davin (International Journal of Research in Medical Sciences, 2017)
Background: Occupational stress is becoming a universal concern. It is no longer taken as a private problem that should be managed alone. Since it affects all categories of workers, it is currently considered an issue that needs to be tackled by the employer, industry and nation as a whole in order to not face a compromise in manpower and occupational productivity. Methods: The present study was a cross sectional, community based descriptive study. A total of 248 KSRTC employees of Dakshina Kannada district were included as part of the study. A Pre structured and pre tested and validated questionnaire for socio-demographic details, the Indian Diabetes Risk Score (IDRS) questionnaireand the AIS (The American Institute of Stress) Workplace Stress Survey questionnairewere used for data collection. Results: Majority of the employees were male and in the age range of 23-59 years. Using the Indian Diabetes Risk score, screening was done for diabetes and 19 cases were identified among the population. 55 cases of Hypertension were also identified and were referred to higher centers and started on treatment for the same. Almost all the study have stress of varying levels subjects had irregular eating habits, lack of exercise and lack of sleep. All the workers were found to have stress, with a majority of them using alcohol and tobacco as a means of coping with stress. Conclusions: Very few studies have been conducted to assess stress levels in organized sectors in India and Karnataka. Hence the present study was undertaken to assess the stress levels and associated health disorders amongst the KSRTC workers of Dakshina Kannada district and to suggest suitable measures to improve occupational health, if necessary.